PENGARUH PEMBERIAN QUERCETIN TERHADAP KADAR LEPTIN SERUM TIKUS WISTAR YANG DIBERI DIET TINGGI LEMAK - ., Sudiarto; Suprihatin, Sri Hidayati (Universitas Muhammadiyah Malang, 2010)
Obesity, one of the degenerative diseases, is a risk factor for chronical disease and an ultimate cause of metabolic syndrome which ismarked by the raising level of leptin on blood (hyperleptinemia). Metabolic syndrome is marked by the size of the waist is more than 40 inchfor man or 35 inch for woman, hypertension, hyperglycemia, high level of triglyceride, and the level of HDL (high-density lipoprotein) is low.This research is aimed to know the giving of quercetin (which has high anti oxide activities) on the declining level of leptin to the giving of DIO(Diet Induced Obesity). An experimental study using Post Test Control Group was done to the experimental wistar rats. Samples werechosen by using randomized complete block design. Rats were treated for 8 weeks. The dose of given quercetin were 2 mg/kgBB/day, 10mg/kgBB/day, and 50 mg/kgBB/day during the last 8 weeks of research. The variable measured in this research is the level of leptin onblood. Based on the experiment, quercetin is proven that gives influence to the level of leptin on obesity wistar rats’ serum compare to the givenlevel of leptin on controlled rats. There is different average on the level of leptin on wistar rats’ serum which being obesity on each grouptreatment. The giving of quercetin have significant correlation (p<0.05) with the level of leptin on wistar rats’ serum which being obesity (r = -0.704, p = 0.001). The conclusion from this research is the giving of quercetin to obesity rats for 8 weeks can decline the level of leptin onblood.Keywords: quercetin, leptin, high fat diet